EXAMINING RESEARCH SPACES IN DOCTORAL PROSPECTUSES - Yazid Basthomi (TEFLIN, 2009)
Abstract: Genre analyses and contrastive rhetoric studies have dealt with quite a number of genres of writing. However, genre analysts and contrastive rhetoric researchers have not carried out adequate analyses of doctoral prospectuses. This paper will, subsequently, address this issue by analyzing a genre of texts of doctoral prospectuses. The analysis will be focused on the sub-genre of Ã¢â¬ÅBackground of the StudyÃ¢â¬Â of the prospectuses. Limitations of accessibility, however, have led this study to only focus on analyzing fourteen doctoral prospectuses written in English by Indonesian students of EFL accessible from the Graduate Program, State University of Malang, Indonesia. This situation suggests that the present study is preliminary. Preliminary, notwithstanding, the study will contribute to filling the gap of the under-researched issue of doctoral studies in Indonesia, particularly, those pertinent to the area of ELT. The analysis shows a tendency that the texts of Background of the Study do not show research spaces. Relevant to this, the article provides an interpretive explanation of the possible factors attributable to this issue.